2006
DOI: 10.1139/t06-009
|View full text |Cite
|
Sign up to set email alerts
|

Results from long-term measurement in piles of drag load and downdrag

Abstract: Several full-scale, long-term tests on instrumented piles performed since the 1960s and through the 1990s are presented. The results of the tests show that a large drag load will develop in piles installed in soft and loose soils. The test cases are from Norway, Sweden, Japan, Canada, Australia, United States, and Singapore and involve driven steel piles and precast concrete piles. The test results show that the transfer of load from the soil to the pile through negative skin friction, and from the pile back t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(25 citation statements)
references
References 8 publications
0
24
0
1
Order By: Relevance
“…Field tests and model tests focused on dragload (additional compressive force caused by NSF) of piles subjected to surcharge load were analyzed (Okabe, 1977;Shibata et al, 1982;Combarieu, 1985;Fellenius, 2006;Yang et al, 2009;Wang et al, 2011;Kim and Chung, 2012). These research results show that dragload is influenced by pile-soil interface coefficients, and soil consolidation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Field tests and model tests focused on dragload (additional compressive force caused by NSF) of piles subjected to surcharge load were analyzed (Okabe, 1977;Shibata et al, 1982;Combarieu, 1985;Fellenius, 2006;Yang et al, 2009;Wang et al, 2011;Kim and Chung, 2012). These research results show that dragload is influenced by pile-soil interface coefficients, and soil consolidation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…NSF reduces pile bearing capacity and increases axial force and settlement, leading to serviceability problems (Li 2014). Based on filed experiments, Fellenius (2006) observed that NSF can produce additional pile axial force for more than 3000kN. Walker and Darvall (2013) reported that surcharge loading could lead to 35mm ground settlement and NSF developed to the depth of 18m in single pile foundation.…”
Section: Introductionmentioning
confidence: 99%
“…Based on full-scale pile test within 1960s~1990s, Fellenius (2006) reported that pile-soil skin friction increased significantly, besides, the neutral point came up with the dissipation of pore water pressure. The NSF development characters for friction pile are studied by centrifuge tests (Lam et al 2009;Ng et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The AASHTO specifications recommend adding the factored drag load from the soil layers above the liquefying layer to the factored loads from the structure and requires the factored shaft resistance in the soil layers below the liquefying layer plus the factored toe resistance to be equal or larger than the combination of the factored loads mentioned. However, the AASHTO specifications do not recognize that a drag load is typically present in the pile prior to the earthquake (Fellenius 2006) Geotechnical and Geoenvironmental Engineering, Vol. 134, No.…”
Section: Introductionmentioning
confidence: 99%